Good living and family farming in the Totonacapan of Puebla, Mexico - Mauricio Torres-Solís; Benito Ramírez-Valverde; José Pedro Juárez-Sánchez; Mario Aliphat Fernández; Gustavo Ramírez Valverde (Íconos)
The search for an answer to the contemporary civilizational crisis, makes it necessary to examine recent proposals originated in Native American ideas about Good Living and forms of social responsibility based on an adequate relationship between human societies and nature. This document describes part of the traditional practices of the Mexican indigenous Totonac group in the municipality of Huehuetla, Puebla. Their holistic scientific approach to food production is highlighted, together with established complementarity relations between families and reciprocity towards spiritual entities. These are seen as crucial in maintaining harmony between a productive habitat and communal existence. Participant observation, systematical interviews and surveys were employed as the main methods which allowed the recognition of the sociocultural symbolisms with which the people of Huehuetla interpret their known world. Thus, Tapaxuwan Latamat (Life in Happiness), -the central notion of the Totonac life-, is described and is shown to be buttressed by the experience of coexisting, working, and celebrating the rituality inherent in Nature. This allows them to remain aware of the existence of a living and sacred territory, where even agricultural and livestock practices are exercised as relationships of coexistence and respect of humans with the entities that inhabit and care for the environment and safeguard their sustenance.